The Possible Role of IVIG in the Treatment of Atrial Fibrillation Accompanied by Fulminant Myocarditis in a 12-Year-Old Pediatric Patient - Can Yilmaz Yozgat; Osman Yesilbas; Selcuk Uzuner; Nigar Bayramova; Gokce Ergun; Lala Nurmammadova; Eser Tekin; Hafize Otcu Temur; Yilmaz Yozgat (Hindawi Limited, 2021)
Background. Fulminant myocarditis (FM) is a potentially lethal condition in children due to rapid progressive hemodynamic instability and cardiogenic shock. Patients with FM might show different clinical manifestations on emergency department admission. Case. Herein, we describe the case of a 12-year-old girl who was admitted to our institution's emergency department due to complaints of abdominal pain and incessant vomiting. However, we detected an early onset of atrial fibrillation (AF) accompanied by FM. The patient's condition of AF and severe hemodynamic disorder was successfully treated in our institution's pediatric intensive care unit. Conclusion. To the best of our knowledge, this is the first report of the co-occurrence of FM and AF successfully treated in childhood. This case report will serve as a guide for the treatment of cases with FM accompanied by AF.